First record of the family Ithonidae (Neuroptera) from Baltic amber - Makarkin, Vladimir N.; Wedmann, Sonja; Weiterschan, Thomas (Zootaxa, 2014)
Elektrithone expectata gen. et sp. nov. (Neuroptera: Ithonidae) is described from Eocene Baltic amber and represents the first record of this family from Baltic amber. The forewing venation of the new genus is characterized by a small number of crossveins as found in some ‘polystoechotid’-like genera, and by the absence of the distal nygma and the strong reduction of the anal area which are characteristic of ‘rapismatid’-like ithonids.